Recurrent parent genome recovery analysis in a marker-assisted backcrossing program of rice (Oryza sativa L.) - Miah, Gous; Yusop, Mohd Rafii; Ismail, Mohd Razi; Puteh, Adam; Harun, Abdul Rahim; Abdul Latif, Mohammad (Elsevier Masson, 2015)
Backcross breeding is the most commonly used method for incorporating a blast resistance gene into a rice cultivar. Linkage between the resistance gene and undesirable units can persist for many generations of backcrossing. Marker-assisted backcrossing (MABC) along with marker-assisted selection (MAS) contributes immensely to overcome the main limitation of the conventional breeding and accelerates recurrent parent genome (RPG) recovery. The MABC approach was employed to incorporate (a) blast resistance gene(s) from the donor parent Pongsu Seribu 1, the blast-resistant local variety in Malaysia, into the genetic background of MR219, a popular high-yielding rice variety that is blast susceptible, to develop a blast-resistant MR219 improved variety. In this perspective, the recurrent parent genome recovery was analyzed in early generations of backcrossing using simple sequence repeat (SSR) markers. Out of 375 SSR markers, 70 markers were found polymorphic between the parents, and these markers were used to evaluate the plants in subsequent generations. Background analysis revealed that the extent of RPG recovery ranged from 75.40% to 91.3% and from 80.40% to 96.70% in BC1F1 and BC2F1 generations, respectively. In this study, the recurrent parent genome content in the selected BC2F2 lines ranged from 92.7% to 97.7%. The average proportion of the recurrent parent in the selected improved line was 95.98%. MAS allowed identification of the plants that are more similar to the recurrent parent for the loci evaluated in backcross generations. The application of MAS with the MABC breeding program accelerated the recovery of the RP genome, reducing the number of generations and the time for incorporating resistance against rice blast.